The irreducibility of the passions in Descartes - Andrade, Érico (2023)
This article presents an alternative vision of the debate on the Cartesian dualism of mind and body. It is argued that the Cartesian dualism of substances does not serve to explain the human condition, which is notably marked by the compound mind and body. In this way I will try to show that the passions or emotions responsible for our mental states are derived from the interaction between the mind and the body, and can in no way be reduced to the mind or body taken separately. They are properties that emerge, in the heterodox sense of the term emergence, from the relation of the mind to the body.